Development and evaluation of a high performance T1‐weighted brain template for use in studies on older adults. Issue 6 (15th January 2021) - Ridwan, Abdur Raquib; Niaz, Mohammad Rakeen; Wu, Yingjuan; Qi, Xiaoxiao; Zhang, Shengwei; Kontzialis, Marinos; Javierre‐Petit, Carles; Tazwar, Mahir; ,; Bennett, David A.; Yang, Yongyi; Arfanakis, Konstantinos
Abstract: Τhe accuracy of template‐based neuroimaging investigations depends on the template's image quality and representativeness of the individuals under study. Yet a thorough, quantitative investigation of how available standardized and study‐specific T1‐weighted templates perform in studies on older adults has not been conducted. The purpose of this work was to construct a high‐quality standardized T1‐weighted template specifically designed for the older adult brain, and systematically compare the new template to several other standardized and study‐specific templates in terms of image quality, performance in spatial normalization of older adult data and detection of small inter‐group morphometric differences, and representativeness of the older adult brain. The new template was constructed with state‐of‐the‐art spatial normalization of high‐quality data from 222 older adults. It was shown that the new template (a) exhibited high image sharpness, (b) provided higher inter‐subject spatial normalization accuracy and (c) allowed detection of smaller inter‐group morphometric differences compared to other standardized templates, (d) had similar performance to that of study‐specific templates constructed with the same methodology, and (e) was highly representative of the older adult brain. Abstract : The purpose of this work was to construct a high‐quality standardized T1‐weighted template specifically designed for the older adult brain, and systematically compare the new template to several other standardized and study‐specific templates in terms of image quality, performance in spatial normalization of older adult data and detection of small inter‐group morphometric differences, and representativeness of the older adult brain. The new template was constructed with state‐of‐the‐art spatial normalization of high‐quality data from 222 older adults. It was shown that the new template a) exhibited high image sharpness, b) provided higher inter‐subject spatial normalization accuracy and c) allowed detection of smaller inter‐group morphometric differences compared to other standardized templates, d) had similar performance to that of study‐specific templates constructed with the same methodology, and e) was highly representative of the older adult brain.